Alkitab di Era Society 5.0: Soft Copy atau Hard Copy - Melvin Berlianno Setiawan; Suhadi Suhadi (Jurnal Teologi Berita Hidup, 2023)
AbstractPeople is currently in the era of society 5.0, which makes human life inseparable from digital technology. The influence of digitalization also occurs in the use of the Bible, which makes people less likely to bring physical Bible to church. Even Church’s Preachers also began to preach using gadgets rather than the physical Bible. Although the use of the digital Bible dates back decades, it is still a matter of debate among Christians today. Some people think that the hard copy Bible is holier than the soft copy Bible. This research is a library research of the sanctity of the Bible in relation to the medium of writing the Bible which is seen from a historical perspective. The soft copy Bible is the latest technological development, just as the hard copy Bible is also the development of modern printing technology. The sanctity of the Bible is not judged by the medium used, because both use a different medium from the original Bible which in its writing uses the medium of stone, clay, ostraca, papyrus, parchment and vellum. Rather it is the authority of the Bible that comes from the inspiration of God (theopneustos) that determines the sanctity of the Bible.Keywords: softcopy Bible; hardcopy Bible; Bible’s sanctityAbstrakMasyarakat saat ini sedang berada di era society 5.0, yang membuat kehidupan manusia tidak dapat dipisahkan dengan teknologi digital. Pengaruh digitalisasi juga terjadi dalam penggunaan Alkitab, yang membuat masyarakat cenderung tidak lagi membawa buku Alkitab ke gereja. Bahkan Pemberita Firman di gereja juga mulai meninggalkan Alkitab berbentuk buku dan menggunakan gawai (gadget) untuk berkhotbah. Walaupun penggunaan Alkitab digital sudah dimulai sejak beberapa dekade yang lalu, tetapi hingga saat ini hal ini masih menjadi perdebatan di kalangan Kristen. Sebagian orang menganggap bahwa Alkitab dalam bentuk buku (Alkitab hard copy) lebih suci dibandingkan dengan Alkitab digital (Alkitab soft copy). Penelitian ini merupakan studi kepustakaan mengenai kesucian Alkitab dalam kaitannya dengan media penulisan Alkitab yang dilihat dari aspek sejarah. Alkitab soft copy merupakan perkembangan teknologi mutakhir, demikian pula Alkitab hard copy juga merupakan perkembangan teknologi percetakan modern. Kesucian Alkitab tidak dinilai dari media yang digunakan, karena keduanya menggunakan media yang berbeda dengan Alkitab aslinya yang dalam penulisannya menggunakan media batu, tanah liat, ostraka, papirus, perkamen dan vellum. Melainkan otoritas Alkitab yang berasal dari ilham Allah (theopneustos) yang menentukan kesucian Alkitab.Kata-kata kunci: Alkitab softcopy; Alkitab hardcopy; kesucian Alkitab